Circular dichroism enhancement in large DNA aggregates simulated by a generalized oscillator model - Andrushchenko, Valery; Bour, Petr (Journal of computational chemistry, 2008)
An increased circular dichroism (CD) signal of large molecular aggregates formed upon DNA condensation was observed a long time ago, and is often referred to as psi-CD. The effort to understand this phenomenon is further motivated by the latest DNA packing studies and advances in macromolecular chemistry. In the present work, the transition dipole coupling model describing interactions of molecules with light has been extended to handle systems of arbitrary size. The analytical formulae obtained retain the simplicity and computational speed of the standard approach. The origin of the psi-effect was investigated on several model systems. The results suggest that the CD enhancement is primarily caused by delocalized phonon-like excitations in nucleic acid strands. The size of the system exhibiting the effect thus does not need to be comparable with or greater than the wavelength of the absorbed light. Small structural irregularities still allow for the enhancement while a larger disorder breaks it. The modeling is consistent with previous experimental electronic and vibrational CD studies, and makes it possible to correlate the enhancement with the geometry of the nucleic acid systems.
Keywords: dimerizace; Biological Clocks; Circular Dichroism; Models, Molecular; DNA; cirkulární dichroismus; biologické hodiny; akustika; Dimerization; Acoustics; Vibration; molekulární modely; vibrace